DINAMIKA PENGUSAHA INDUSTRI COR LOGAM DI MASA KRISIS - Susi Eja Yuarsi (Populasi, 1999)
Initially, metalworking can be quite reliable because, besides its substantial contribution to the economic progress of the local population, it has also absorbed a very substantial proportion of labor force, both local and from other districts. From the onset of the current economic crisis, metalworking has experienced a tremendous decline. This has been mainly due to the high production cost, which can not be compensated by the low selling price. The undesirable consequence of this trend is that many entrepreneurs have been forced out of business, hence, stopped production. The few who have persisted in business must really strain themselves for the sake of business survival. Their effort is mainly to keep the production cost as low as possible. This can be achieved by reducing the quantity of raw materials used, closer and tighter monitoring of the production process, and changing the system of paying workers. Although these efforts have been applied, the limited number of orders that they receive has forced most of the entrepreneurs to suspend production. There is therefore, an urgent need to seek alternative solutions to this pressing problem.